A porous MOF-derived NiMn2O4 material and its superior energy storage performance for high-performance supercapacitors. (7th March 2022) - Yuan, Hao; Yuming, Guo; Jiang, Linghong
Abstract : A binder-free C@NiMn2 O4 electroactive material was prepared through the calcination of a pristine Ni, Mn-MOF at 600 °C for 4 h. The fabricated C@NiMn2 O4 /NF electrode exhibits an area specific capacitance of 5.39 F cm −2 at 2 mA cm −2 . Abstract : In this work, we synthesized Ni, Mn-metal–organic framework (MOF) and C@NiMn2 O4 materials on the surface of a nickel foam (NF) support via a simple and scalable cathodic electrochemical deposition (CED) strategy, followed by heat treatment. The structures and morphologies of the Ni, Mn-MOF and C@NiMn2 O4 materials were characterized by powder X-ray diffractometry, Fourier-transform infrared spectroscopy, thermogravimetric analysis, and field-emission scanning electron microscopy techniques. The prepared bimetallic Ni, Mn-MOF was found to have a flower-like morphology and its derived C@NiMn2 O4 product showed hierarchical star-like morphology. Both of these morphologies can provide favourable paths for electrolyte ion penetration, resulting in an enhanced contact area between the active material and electrolyte. The obtained products need no additional treatments and can be directly used as a binder-free electrode material. The charge storage capabilities of the electrodes were evaluated by cyclic voltammetry, charge–discharge cycling and electrochemical impedance spectroscopy in an aqueous alkaline electrolyte (6 M KOH) employing a three-electrode system (half-cell) configuration. A specific capacitance of as high as 1025 F g −1 was measured for the C@NiMn2 O4 /NF electrode, which was higher than that of the pristine Ni, Mn-MOF/NF electrode (641 F g −1 ), at a current density of 1 A g −1 . The fabricated C@NiMn2 O4 /NF electrode exhibited high rate capability (66% capacity retention at 1 to 30 A g −1 ) and good cycling stabilities of 89.6% and 73.5% after 10 000 cycles at current densities of 2 and 5 A g −1, respectively. The observed outstanding performance of C@NiMn2 O4 was assigned to its porous texture as well as the presence of carbon particles, which facilitate electrolyte ion transportation and electron transfer. And, the hierarchical star-like microstructure directly grown on the NF exhibits satisfactory active sites for redox reactions to occur, leading to excellent electrochemical performance. These results show that the C@NiMn2 O4 /NF electrode could be a promising candidate for use in energy storage.